2000
DOI: 10.2106/00004623-200004000-00027
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug Resistance-1 and P-glycoprotein in Human Chondrosarcoma Cell Lines: Expression Correlates with Decreased Intracellular Doxorubicin and In Vitro Chemoresistance

Abstract: Summary:We report on two chondrosarcoma cell lines, FS and AQ, that may be used as models of multidrug resistance in chondrosarcoma. Multidrug resistance-1 expression was assayed with reverse transcriptionpolymerase chain reaction. Immunostaining for the multidrug resistance-1 product, P-glycoprotein, was performed with the monoclonal antibody C494. Intracellular levels of doxorubicin were measured by fluorescent emission at 590 nm after 1 hour of incubation with the agent and again after 1,2, and 4-hour washo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…Previous studies demonstrated that several CS cell lines overexpress efflux pumps or anti-apoptotic proteins, reducing their sensitivity to DOX or CIS. 12,13 For instance, OUMS27 or SW1353 cells in monolayer had IC50 values for these drugs between 5 and 400 mM, 13 ie 10-100 folds higher than the IC50 values calculated here. This discrepancy could be explained by the use of different cell lines, passages, culture conditions, and/or drug formulation.…”
Section: Chondrogenesis and Chemoresistance D Monderer Et Alcontrasting
confidence: 66%
See 1 more Smart Citation
“…Previous studies demonstrated that several CS cell lines overexpress efflux pumps or anti-apoptotic proteins, reducing their sensitivity to DOX or CIS. 12,13 For instance, OUMS27 or SW1353 cells in monolayer had IC50 values for these drugs between 5 and 400 mM, 13 ie 10-100 folds higher than the IC50 values calculated here. This discrepancy could be explained by the use of different cell lines, passages, culture conditions, and/or drug formulation.…”
Section: Chondrogenesis and Chemoresistance D Monderer Et Alcontrasting
confidence: 66%
“…High expression of multidrug resistance (MDR) pumps could be implicated to export the drugs from within the cells, and the role of ABCB1 gene product P-glycoprotein 1 (also known as MDR1) in resistance of a CS cell line to doxorubicin (DOX) has been demonstrated. 12 The low proliferation rates of CS cells may also limit the efficacy of chemotherapeutic agents, which target more specifically actively dividing cells. 9 Moreover, there is evidence that CSs overexpress several anti-apoptotic genes such as BCL-2 or Survivin (also known as BIRC5), preventing cell death induced by conventional chemotherapy.…”
mentioning
confidence: 99%
“…An additional explanation for this chemotherapy resistance may be expression of the multidrug-resistance 1 gene, Pglycoprotein, resulting in resistance to doxorubicin in vitro [76]. Moreover, the access of anticancer agents may be hampered by the large amount of extracellular matrix and the poor vascularity, implying that the agents have to diffuse over a relatively long distance in order to reach the tumor cells.…”
Section: Systemic Treatmentmentioning
confidence: 99%